Final Report-Consolidated SI Information for Sarawak Soil Database - Norazzlina, M.Sa'don; Abdul Razak, Abdul Karim; Bong, Chih How; Siti Noor Linda, Taib; Chua, Stephanie Hui Li; Alsidqi, Hasan; Ahmad Kamal, Abdul Aziz; Wong, Linda Lin Juan; Louisa Dubah, Hubert Chunggat (Sarawak Multimedia Agency (SMA), 2020)
The development of digitized Consolidated Sarawak Geotechnical Site Investigation (CoSI) database @Sarawak-Soil aims to enable information to be stored in a digital format rather than static images and retrieved fast with the efficient search. The CoSI database is a function of a database management system, which consists of the site information; includes the project name, location (division), borehole logs, field and laboratory test results. A data entry template was designed for the conversion of all the existing hard copies of boreholes information and future new collected borehole logs into a soft-copy format. This CoSI database is deployed as a web based system which provides various opportunities to explore the published data and can be accessed anywhere through the computer and smart phones with internet access.